Pengaruh Kualitas Pelayanan, Fasilitas, dan Daya Tarik Wisata Terhadap Kepuasan Pengunjung Agrowisata Bhumi Merapi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
The aims of this study is to determine the effect of service quality, facilities, and tourist attractions of visitor satisfaction at Agrowisata Bhumi Merapi. This study is a survey research using a questionnaire to collect data. Samples were taken of 60 respondents using purposive sampling techniques. This study was analyzed by validity and reliability test, multiple linear regression, hypothesis test through t-test and F test as well as coefficient determination analysis (R2) by SPSS program with the level error of significance is 0.05. The results of the research showed that parttialy the service quality, facilities, and tourist attractions influence has a positive effect the level of visitor satisfaction at Agrowisata Bhumi Merapi. Simultaneously, variables of service quality, facilities, and tourist attractions have significant influence on visitor satisfaction, which is proven by the score of F as much as 41,383 at significance value 0,000 < 0,05. Adjusted R Square (R2) in this study is 0.672 or 67.2%.